Community voices: sowing, germinating, flourishing as strategies to support inclusion in STEM - Luisa Maria Diele-Viegas; Thamara Santos de Almeida; Iris Amati-Martins; Christine D. Bacon; Cibele Cassia-Silva; Rosane G. Collevatti; Jéssica Fenker; Tabata Elise Ferreira Cordeiro; Giuliana Caldeira Pires Ferrari; Ana Clara Sampaio Franco; Luiza Flores Gasparetto; Juliana Hipólito; et al. (Nature Communications, 2022)
Understanding gaps in academic representation while considering the intersectionality concept is paramount to promoting real progress towards a more inclusive STEM. Here we discuss ways in which STEM careers can be sown and germinated so that inclusivity can flourish.